Movimentos de renovação política e juventude: sentimentos partidários e democracia em cheque - Campos, Daniele Olimpio de (2023)
Aren't young people responsible for the future of our country? Inspired by this question, the research carried out here aims to analyze how young people belonging to Political Renewal Movements understand and participate in Brazilian democratic processes, and above all, how they perceive the crisis of political representation and partisan sentiments. To this end, a case study was carried out focusing on the analysis of two Renovation Movements, Bancada Ativista, and RenovaBR, chosen because they concentrate young participants from multiple ideological and partisan aspects. This study is divided into three phases, including the cataloging of all participants and former participants of the respective movements and the carrying out of semi-structured interviews with young people from the chosen organizations. Furthermore, from the literature research, conceptual elements were added to understand the entire context of the creation and development of Political Renewal Movements in Brazil and their relationships with Brazilian youth.